LEVEL OF GRADATION IN LINGUISTIC TERMS "SPIRITUAL MAN" AND "KOMIL INSON” - Akhmedova Mehrinigor Bahodirovna (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2023)
Despite the fact that the definition of the terms "spiritual man" and "komil inson” are connected with the concept of "spirituality" in both English and Uzbek language there have been different views how these two terms are different by their usage. As it is seen from the analyses, both words show the last stage of being perfect and connected with high spirituality.